Differences In Level Of Spiritual Well-Being Of Patients With Type 2 Diabetes Mellitus In Urban And Rural Areas - Suyanto Suyanto; Sri Lestari Dwi Astuti (Poltekkes Kemenkes Surakarta, 2022)
Background: Patients with Type 2 Diabetes Mellitus (T2DM) require a prolonged treatment time so that their condition can get worse. This incident is related chiefly to spiritual well-being disorders such as boredom and hopelessness, which results in decreased Diabetes management. The study aims to analyze differences in the spiritual well-being level of T2DM patients in urban and rural areas. Methods: Quasi-experimental method with a two-group pre-post-test design without control was employed in this study. The population in the rural area were T2DM patients in Matesih Subdistrict, and the population in the urban area were members of the Persadia Ngringo unit whose. Samples were taken using purposive sampling, obtaining 120 people. Data were collected using the SWBS questionnaire made by Ellison and modified with a validity of 0.803 and reliability of 0.911. After the pretest was carried out, the respondents were given a pocketbook and lectures on how to maintain spiritual well-being. Then, a posttest was conducted, obtaining normality of 0.93, causing the data to be analyzed using a t-test. Results: The spiritual well-being of people with T2DM in villages was 40% higher than those living in cities. The results of the t-test obtained a significant value of 0.04. Conclusion: There are differences in the spiritual well-being of T2DM patients in urban and rural areas. Attention and support to the spiritual well-being of T2DM patients should be given to carry out diabetes management properly.